2021
DOI: 10.3847/1538-4357/ac0eef
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless Equilibria in General Relativity: Stable Configurations beyond the First Binding Energy Maximum

Abstract: We numerically study the stability of collisionless equilibria in the context of general relativity. More precisely, we consider the spherically symmetric, asymptotically flat Einstein–Vlasov system in Schwarzschild and maximal areal coordinates. Our results provide strong evidence against the well-known binding energy hypothesis, which states that the first local maximum of the binding energy along a sequence of isotropic steady states signals the onset of instability. We do, however, confirm the conjecture t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…The dynamical instability of a self-gravitating sphere in the context of GR has been explored long ago by [23,24] and Zel'dovich & Podurets (1966) [25], via the study of pulsation equation and binding energy, respectively. It was found that the turning point of fractional binding energy [26,27] is very close to the result using the pulsation equation [28]. Chandrasekhar's criteron [23,24] provides a sufficient condition triggering the black hole formation.…”
Section: Introductionmentioning
confidence: 55%
“…The dynamical instability of a self-gravitating sphere in the context of GR has been explored long ago by [23,24] and Zel'dovich & Podurets (1966) [25], via the study of pulsation equation and binding energy, respectively. It was found that the turning point of fractional binding energy [26,27] is very close to the result using the pulsation equation [28]. Chandrasekhar's criteron [23,24] provides a sufficient condition triggering the black hole formation.…”
Section: Introductionmentioning
confidence: 55%
“…However, recent numerical evidence [20] strongly contradicts this hypothesis and shows that stability behaviors can be much more diverse than previously thought. As already stated by Ipser and Thorne [27], new versatile criteria are needed in order to gain more understanding of stability issues in general relativity.…”
Section: Steady States and Previous Stability Resultsmentioning
confidence: 89%
“…
We consider the spherically symmetric, asymptotically flat Einstein-Vlasov system in maximal areal coordinates. The latter coordinates have been used both in analytical and numerical investigations of the Einstein-Vlasov system [3,8,18,19], but neither a local existence theorem nor a suitable continuation criterion has so far been established for the corresponding nonlinear system of PDEs. We close this gap.
…”
mentioning
confidence: 99%
“…The system as stated above has been used both in analytical and numerical investigations, cf. [3,8,18,19], even though the switch to Cartesian coordinates is not done in all of these papers, and the momentum variable v is sometimes replaced by…”
mentioning
confidence: 99%
See 1 more Smart Citation